Mathematical modelling of allelopathy: II. The dynamics of allelochemicals from living plants in the environment - An, M.; Liu, D.L.; Johnson, I.R.; Lovett, J.V.
The contents of allelochemicals in living plants, and their fate and dynamics in environment are an important aspect in the study of allelopathy. A mechanistic model developed proposes that there are two kinds of allelochemical productions in a plant, which are dictated by age and plant stress, and are reflected by the corresponding dynamics in the environment. The decline of allelochemical contents in living plants with increasing age of plants may be a general case, while periodic production may be a special case. The ecological roles of such phenomena in plant allelopathy are discussed.
Keywords: ALLELOPATHY; ALLELOCHEMICALS; MATHEMATICAL MODELLING; PLANT DEFENCE; STRESS